Structure and properties of coatings based on FeCrAl and Cr18Ni10T - Belous, V.А.; Bortnitskaya, М.A.; Vasilenko, R.L.; Voyevodin, V.N.; Klimenko, І.О.; Kovalenko, V.І.; Kolodiy, І.V.; Kuprin, A.S.; Marinin, V.G.; Ovcharenko, V.D.; Tikhonovsky, М.А. (Вопросы атомной науки и техники, 2020)
The process of vacuum-arc deposition of protective coatings from multicomponent FeCrAl cathodes and 18Cr10NiT stainless steel onto fragments of Zr1Nb alloy claddings has been developed. The influence of the reaction atmosphere (vacuum, nitrogen, oxygen) during the deposition of coatings on their structure, mechanical and corrosion properties is investigated. Coatings deposited in vacuum from the Cr18Ni10T cathode have the best set of mechanical properties and corrosion resistance; whereas coatings based on FeCrAl require composition optimization. It has been established that coatings deposited from FeCrAl and stainless steel cathodes with a thickness of 20 μm significantly increase oxidation resistance and prevent the destruction of fuel cladding under exposure to air at 1150 ℃ for 1 h.